Pengaruh Pemberian Konsentrat yang Mengandung Rumput Laut (Eucheuma cottonii) Afkir Terfermentasi Terhadap Konsumsi dan Kecernaan Nutrien Serta Total Digestible Nutrient Sapi Bali Betina Muda yang Diberi Pakan Dasar Silase Rumput atau Fodder Jagung - Kedhi, Theodorus; Jelantik, I Gusti Ngurah; Jalaludin (Yayasan Sumber Daya Manusia Cerdas, 2025)
The aims of this experiment was to investigate the effect of feeding concentrates containing fermented rejected seaweed (ECOT) on the intake and digestibility of nutrients and the total digestible nutrients of young female bali heifer maintained on silage or corn fodder basal diets. A total of 4 bali heifer were used in this experiment following a latin square design (LSD) consisting of 4 treatments and 4 periods as replications. The treatments were SKC0 = grass silage 60% + concentrate containing unfermented ECOT 40%, SKC0F = grass silage 60% + concentrate containing fermented ECOT 40%, FJKC0 = corn fodder 60% + concentrate without fermentation 40%, FJKC0F = corn fodder 60% + fermented concentrate 40%. The variables measured were the intake and digestibility and total digestible nutrients. The data obtained was analyzed using analysis of variance and Duncan Multiple Range Test to see the different between treatments. Results showed that the intake CP has a significantly affected (P<0,05) while the intake of CF does not significantly (P>0,05) and the digestibility of CP, CF and TDN has a significantly affects (P<0,05). The conclusion is that fermented E. cottonii reduces CP in silage and increases it in corn fodder, while the creasing the intake and digestibility of CF and TDN from both the grass silage and corn fodder base feed materials.